2021
DOI: 10.3390/ijerph18168319
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of Oral Leukoplakia in Female Patients—Analysis of Risk Factors Related to Treatment Outcomes

Abstract: Background: The aim of this study was to make a comparison of clinicopathological characteristics of oral leukoplakia between male and female patients following carbon dioxide laser excision for oral leukoplakia and analyze the factors associated with the treatment outcomes in female patients. Methods: Medical records of patients with oral leukoplakia receiving laser surgery from 2002 to 2020 were retrospectively reviewed and analyzed statistically. Results: A total of 485 patients were enrolled, including 412… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Concerning gender distribution, the results showed that females affected with oral epithelial dysplasia (52%) more than males (48%). Similar finding reported in other parts of the world [17] that revealed there is no gender predilection was found, but, in contrast to our study [18] showed that (80%) of oral dysplastic samples belonged to males with M:F 4:1. There is controversy as to which gender is most affected.…”
Section: Discussionsupporting
confidence: 86%
“…Concerning gender distribution, the results showed that females affected with oral epithelial dysplasia (52%) more than males (48%). Similar finding reported in other parts of the world [17] that revealed there is no gender predilection was found, but, in contrast to our study [18] showed that (80%) of oral dysplastic samples belonged to males with M:F 4:1. There is controversy as to which gender is most affected.…”
Section: Discussionsupporting
confidence: 86%
“…[3][4][5][6][7][8] Tobacco use is among one the etiological factors of oral leukoplakia. 9,10 . Tobacco is used in the Khyber Pakhtunkhwa province of Pakistan specifically in the form of oral snuff (naswar) which is a smokeless (SL) form.…”
Section: Introductionmentioning
confidence: 99%